Tactile Coding System on Tablet Blister Strips for Safe Medicine Use by Visually Impaired and Elderly Patients (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Medication errors are common among visually impaired and elderly patients due to the difficulty in identifying medicines from conventional blister strips. Similar packaging, small printed text, and the absence of tactile features increase the risk of taking the wrong medication or incorrect dose. This project proposes the development of a Tactile Coding System on tablet blister strips to improve safe and independent medicine use. The concept involves incorporating simple raised tactile patterns, such as dots, lines, or geometric symbols, on blister packs to represent specific medicines, dosage strengths, or dosing schedules. These tactile codes can be easily recognized by touch without relying on vision. The system is designed using safe, durable, and cost-effective embossing techniques that do not affect the quality, stability, or integrity of the medicine. Different tactile patterns may also be combined with color coding and QR codes to support caregivers and healthcare professionals. The proposed design aims to reduce medication errors, improve patient confidence, enhance treatment adherence, and promote independence among visually impaired and elderly individuals. The tactile coding system is simple to manufacture, compatible with existing pharmaceutical packaging processes, and suitable for large-scale implementation. This innovative patient-centered packaging approach has the potential to improve medication safety, accessibility, and healthcare quality while supporting inclusive pharmaceutical design and universal healthcare practices.
Keywords: Medication errors; Tactile Coding System; tablet blister strips